Exploring putative therapeutic mechanisms of change in a hybrid compassion-focused, ecological momentary intervention: findings from the EMIcompass trial - Pätzold, Isabell; Schick, Anita; Rauschenberg, Christian; Hirjak, Dusan; Banaschewski, Tobias; Meyer-Lindenberg, Andreas; Böhnke, Jan R.; Boecking, Benjamin; Reininghaus, Ulrich (Behaviour research and therapy, 2023)
Compassion-focused interventions represent a promising transdiagnostic approach, but the mechanisms involved in hybrid delivery combining face-to-face sessions and an ecological momentary intervention remain unexplored. The current study aimed at exploring associations of putative mechanisms with clinical outcomes at post-intervention/follow-up and mediation of outcome at follow-up by preceding pre-to post-intervention changes in putative mechanisms. The compassion-focused EMIcompass intervention was applied in an exploratory randomized controlled trial (treatment as usual (TAU) vs. TAU + EMIcompass) with youth with early mental health problems. Data was collected before randomization, at post-intervention and at four-week follow-up. We recruited N = 92 participants, N = 46 were allocated to the experimental condition. After control for baseline levels of the target outcomes, baseline-to post-intervention improvement in adaptive emotion regulation was associated with lower levels of clinical outcomes (e.g. psychological distress b = −1.15; 95%CI = −1.92 to −0.39) across time points. We could not detect indirect effects, but we observed associations of change in self-compassion and adaptive emotion regulation with outcomes at follow-up in the mediation analysis (e.g., β = −0.35, 95%CI = −0.52 to −0.16). If successfully targeted by interventions, self-compassion and emotion regulation may be promising putative therapeutic mechanisms of change.